Leaching risk of sulfadiazine in soil: Regulatory role of low-molecular-weight organic acids associated with root exudates - Fuxiang Zhang; Jiaxuan Hong; Qiang Fu; Hongliang Jia; Yi-Fan Li; Yongzhen Ding; Xiaoyan Wang; Song Cui; Guorui Liu (Environmental Chemistry and Ecotoxicology, 2025)
Low-molecular-weight organic acids (LMWOAs) are known to influence the environmental behaviors of various pollutants. However, their impact on sulfadiazine (SDZ), a widely detected antibiotic in farmland soil, has not been fully elucidated. This study investigates the effects of LMWOAs (tartaric acid, malic acid, and acetic acid) associated with root exudates on SDZ adsorption and migration in soil. Results show that LMWOAs significantly enhance SDZ adsorption by soil, with this enhancement being pH-dependent. Under acidic conditions (pH 3.2), the adsorption capacity increases by 0.06–0.16 mg·g−1, while under alkaline condition (pH 9.0), it decreases. Notably, when LMWOAs are premixed with soil prior to SDZ addition at pH 9.0, they reduce the adsorption capacity by 91.5 % - 95.0 %, compared to treatments without premixing, likely due to the occupation of adsorption sites and alterations in micropore structure. Leaching experiments further reveal that LMWOAs promote SDZ migration, but high-volume perfusion inhibits this effect, indicating a mass ratio dependence between soil and LMWOAs for SDZ adsorption. Importantly, SDZ leaching results from soil column experiments deviate from model predictions based on parameters obtained from batch adsorption studies, as the model tends to underestimate the leaching potential of SDZ. This discrepancy suggests that dynamic factors such as pH buffering and competitive adsorption should be integrated into predictive models to better reflect real-world field conditions. These findings contribute to deeper understanding of pollutant transfer mechanisms within the soil-water system and offer actionable insights for mitigating antibiotic diffusion risks in farmland through optimized organic amendment strategies and pH regulation. By safeguarding soil and groundwater quality, this approach highlights the critical role of such mitigation strategies in promoting environmental sustainability, particularly in agricultural systems where antibiotic contamination poses a significant threat.